WOMEN’S SEXUALITY AND REPRODUCTIVE RIGHTS – A CRITICAL STUDY - Tanvi Singh (Journal of Legal Studies & Research, 2022)
The term Sexuality is related to a person’s sexual behaviour and feelings, being attracted toward someone physically, sexually or emotionally all these things are part of our sexuality. Women sexuality is very less concerned topic for world specially in the country like India. Why India? It is because may our society give women a prior position like goddesses but still, stuck in that stereotype where women’s need and desire doesn’t concern other at all. We assume she like this or like that but never come up with an idea to simply ask her about what she may actually like or want. All women’s desires cannot be summarized in one, it varies from each woman as an individual. In the interview with BBC news Rutgers University Professor Beverly Whipple says: “Every woman wants something different.” There is need to understand that women may have preference like men do in their sexual life and it’s fine to have, they cannot force to be of one kind irrespective of her choices. Her sexual choices must be respected as an individual choice. A women may like to be with someone one or may not throughout her entire life, or may she like another woman as her partner these all are part of her sexuality. Any individual should not be judge for this. Women’s sexuality may change over time, it is possible for a woman to fell primary attracted to men, but may later feel attracted to women. it is normal like anyone else. The important thing is to feel respected and safe whatever decision you made. The 1995 UN fourth World Conference on women in Beijing define Reproductive rights in a broader context as “The human rights of women include their right to have control over and decide freely and responsibly on matters related to their sexuality, including sexual and reproductive health, free of coercion, discrimination and violence. Equal relationships between women and men in matters of sexual relations and reproduction, including full respect for the integrity of the person, require mutual respect, consent and shared responsibility for sexual behaviour and its consequences”.